Lymphoepithelial cyst mimicking pancreatic cancer: a case report and literature review - Takuya Iguchi; Akira Shimizu; Koji Kubota; Tsuyoshi Notake; Shinsuke Sugenoya; Kiyotaka Hosoda; Koya Yasukawa; Hikaru Hayashi; Ryoichiro Kobayashi; Yuji Soejima (Surgical Case Reports, 2021)
Abstract Background Pancreatic lymphoepithelial cyst (LEC) is a rare nonmalignant cyst consisting of a benign collection of keratinizing squamous epithelial cells with lymphoid tissue. Diagnosing LEC preoperatively is considered difficult because of its non-specific clinical features; therefore, LEC is generally treated the same as a malignant tumor. Case presentation Our case was a 65-year-old man who underwent pancreatoduodenectomy 3 years previously for carcinoma arising from the ampulla of Vater. A pancreatic mass in the remnant pancreatic tail was detected through follow-up abdominal contrast-enhanced computed tomography (CT). This revealed two adjacent ring-enhanced masses that had been in tight contact with the left diaphragm and were enlarged. The tumors had high signal intensity in diffusion-weighted images of magnetic resonance imaging, and fluorodeoxyglucose-positron emission tomography (FDG-PET) showed abnormal uptake (standardized uptake value maximum: 17.4). Therefore, we conducted a partial resection of the remnant pancreas with concomitant resection of the left diaphragm. Microscopically, one of the tumors revealed rare fragments of apparently benign squamous epithelium on a background of keratinous debris, cyst contents, and scattered lymphocytes, and the adjacent mass revealed infiltrated neutrophils. The histopathological diagnosis was an LEC with chronic abscess. The patient recovered uneventfully and was discharged on postoperative day 10. Conclusions We reported a rare case of LEC with chronic abscess that was positively visualized on FDG-PET. When a pancreatic malignancy cannot be excluded, surgical resection is considered inevitable.